Gametogenesis, fertilization and early embryogenesis in mammals with special reference to goat: a review - Abdullah, Ramli; Wan-Khadijah, W.E.; Rahman, A.N.A. (2008)
Embryo in vitro Production (IVP) and associated Assisted Reproductive Technologies (ARTs) in goat, e.g., estrus synchronization and superovulation, Laparoscopic Ovum Pick-up (LOPU), in vitro Maturation (IVM), in vitro Fertilization (IVF), Intracytoplasmic Sperm Injection (ICSI) and in vitro Culture (IVC) attained significant attention in the recent years. However, for the success in any IVP protocols in goat sound knowledge of physiology of gametogenesis, fertilization and early embryogenesis in vivo is crucial because in vivo information form the basis and guide for any in vitro experiment. Unlike human, laboratory animals, cattle and sheep, fewer studies have been conducted in gametogenesis, fertilization and early embryo development in goat. Data for sheep and cattle are mostly used as a basis for goat IVP studies. Therefore, the current study is intended to review gametogenesis, sperm oocyte interaction, fertilization and early embryogenetic process in mammals with special reference to goat. © 2008 Asian Network for Scientific Information.